Distributed fair cooperative routing in multi-gates wireless mesh network - Hong QIAO; Da-fang ZHANG; Kun XIE; Shi-ming HE; Ji ZHANG (Tongxin xuebao)
Existing cooperative routings cannot fairly allocate the wireless resources,which results in that the throughput of minimum flow cannot satisfy the performance requirement.The multiple flow cooperative routing problem is formulated as a convex optimization problem with the goal of maximizing network utility.Based on dual decomposition and subgradient method,a distributed fair cooperative routing algorithm in multi-gates wireless mesh network-FCRMG is proposed.The simulation results show that,FCRMG can largely improve the throughput of the minimum flow without decreasing the total network throughput,compared with uncooperative routing based on expected transmission time metric and cooperative routing based on contention aware metric.